Integrating phosphate-solubilizing fungi and moderate phosphorus application for sustainable corn production - Sigit Prastowo; Distiana Wulanjari; Agung Sih Kurnianto; Ati Kusumawati; Lenny Widjayanthi; Indah Ibanah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Corn (Zea mays) is a vital staple crop and the second-largest agricultural commodity in Indonesia. However, productivity remains suboptimal, often due to nutrient imbalances, particularly in phosphate-rich soils where availability to plants is limited. This study aimed to assess the effects of reducing phosphate fertilizer by 50% in combination with bioagents Trichoderma harzianum, Metarhizium anisopliae, and arbuscular mycorrhizal fungi on key agronomic traits of corn. A randomized block design was employed to measure parameters including root volume, root-to-shoot ratio, leaf width, and seed sphericity. Results showed that applying 50% phosphate fertilizer alone yielded the highest root volume (70.00±18.19 mL) and root-to-shoot ratio (0.50±0.32), suggesting improved root development. In contrast, treatment with Metarhizium produced the widest leaves (10.14±0.30 cm) but showed the lowest values for root volume and root-to-shoot ratio. These findings highlight the potential of combining moderate phosphate input with beneficial bioagents to improve corn performance in marginal soils. The approach offers a cost-effective and environmentally sustainable alternative for managing nutrient imbalances. Further studies on long-term effects and economic feasibility are recommended to support wider adoption of these practices in sustainable agriculture. Keywords: maize; Metharizium; nutrient management; sustainable agriculture; Trichoderma